Human Beings’ Affinity with Nature in Meghadutam - Gouli, Mohan Raj (The Batuk, 2019)
Kalidasa's Meghadutam evokes a strong correspondence between nature and human beings. The poem was composed at a time when there was no any polluted environmental problem created by the inventions of science and technology. It was a time when people passionately lived with nature and worshiped it bringing different images of divinity. Nature was a source of inspiration and people had unshakable trust in it. When human beings were deceived and mistreated or they were in trouble because of their own activities or some other outside problematic agencies, they naturally tried to seek shelter to be with nature.